Rheumatoid meningitis: a rare neurological complication of rheumatoid arthritis - Fan, Siyuan; Zhao, Jiuliang; Hou, Bo; Liu, Mange; Niu, Jingwen; Zhou, Yan; Mao, Chenhui; Ren, Haitao; Feng, Feng; Li, Mengtao; Zeng, Xiaofeng; Zhu, Yicheng; et al. (Frontiers in Immunology, 2023)
Objective To describe the clinical and neuroimaging characteristics of rheumatoid meningitis (RM) in Chinese patients. Methods The patients admitted to our hospital with the diagnosis of RM in the past 8 years were retrospectively analyzed. Results Six patients with RM were identified among 933 patients admitted with rheumatoid arthritis (RA). The symptoms of meningitis occurred after onset of arthritis in five patients and before onset in one. Headache (n=6), hyperacute focal neurological deficits (n=4) and seizures (n=3) were the most prevalent symptoms. The nadir modified Rankin Scale score was ≥3 in five patients. Rheumatoid factor was elevated in all patients, and interleukin-6 levels in cerebrospinal fluid were dramatically elevated in three of four tested patients. Magnetic resonance imaging of the brain revealed that the meninges were affected in all patients and the cerebral parenchyma was affected in one patient. The lesions were generally located in the frontoparietal region and showed restricted diffusion along the adjacent subarachnoid space. RM occurred during disease-modifying therapy in four patients. In the acute episode, three patients improved on tocilizumab and the other three improved on pulse corticosteroids. For maintenance therapy, two patients received combined therapy of tocilizumab and other immunosuppressive agents, one received adalimumab and methotrexate, and two received low-dose oral corticosteroids with an immunosuppressive agent. Five patients had a good outcome, and one died of Pneumocystis jirovecii pneumonia after stabilization of his neurologic conditions. No relapse of RM occurred on immunotherapy during follow-up. Conclusions Chinese patients with RM share some remarkable clinical and neuroimaging features and respond well to appropriate immunotherapy. Tocilizumab could be a treatment option for this severe complication of RA.